The Politics of Hate Speech Akun Fufufafa: Perspektif Etika Komunikasi dan Dampaknya Terhadap Kohesi Sosial - Marpaung, Hery Wahyudi; Sazali, Hasan (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study discusses the phenomenon of political hate speech carried out by anonymous accounts "fufufafa", focusing on the perspective of communication ethics and its impact on social cohesion. Through a qualitative approach and case study method, an analysis was carried out on the content of the account upload using a critical discourse framework. The results of the study show that hate speech conveyed is systematic, attacks the personal aspects of political figures, and is full of ideological content that emphasizes the moral dichotomy between "us" and "them." Communication strategies such as simplification, labeling, framing, and social agitation are used to negatively shape public opinion and reinforce polarization. From the point of view of communication ethics, the act reflects a moral deviation because it ignores the values of empathy, respect, and social responsibility in digital communication. The psychosocial impacts that are caused include the stigmatization of minority groups, emotional trauma to individuals, and fragmentation in online communities. This research emphasizes the importance of digital literacy, strengthening ethical communication regulations, and public participation to prevent the spread of hate speech and maintain social integration in digital democracy. These findings are expected to be an academic and practical contribution in developing strategies for handling hate speech in Indonesia.